The Target Areas of Regional Development, Tool and Institutional Background, its Present and Future Prospects - Harsányi, Endre (Acta Agraria Debreceniensis, 2004)
Regional politics determines the aims of regional structures, and the tools with the institutional background on the whole necessary achieve these. Realizing the aims of regional politics is a precondition of executing the basic principles of regional development and politics. The regional institutional system for handling the decentralized financial resources has not evolved in Hungary yet. The professional institutes for preparing the programs have not been set up, and the management of execution is slowly taking shape. There are still deficiencies in the domestic application of concentration and addition principles. A number of funds are provided on a national level, that are directly or indirectly aimed at regional development. The obvious coordination among the funds is not carried out neither on a national, nor on a regional level, partly to avoid parallel consumption aims. The future of Hungarian spatial structure depends on the type of decentralization strategy the country will follow for the new resources after the accession. Total decentralization offers the most efficient solution for Hungary.